2017
DOI: 10.1037/abn0000287
|View full text |Cite
|
Sign up to set email alerts
|

Networks of loss: Relationships among symptoms of prolonged grief following spousal and parental loss.

Abstract: The death of a loved one can trigger a range of emotional, behavioural, motivational and cognitive reactions collectively labelled as “grief”. There has been a recent resurgence of empirical interest in grief reactions, and there is now a general consensus that 7%–10% of bereaved individuals experience intense and chronic reactions termed Prolonged Grief (PG). However, there is ongoing debate about how best to conceptualise the construct. Recent studies have advanced this debate by applying a network, or causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 46 publications
9
38
2
Order By: Relevance
“…This study used network analysis to explore this issue. Consistent with previous studies, we observed that the symptoms of PGD formed a network of nodes connected by positive edges (Maccallum et al., ; Robinaugh et al., , ). This indicated that the node values were positively associated, independent of other nodes within the network.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study used network analysis to explore this issue. Consistent with previous studies, we observed that the symptoms of PGD formed a network of nodes connected by positive edges (Maccallum et al., ; Robinaugh et al., , ). This indicated that the node values were positively associated, independent of other nodes within the network.…”
Section: Discussionsupporting
confidence: 92%
“…Notwithstanding these issues, the results of this analysis share features with previous network analyses of PGD (Maccallum et al., ) and PCBD (Malgaroli et al., ; Robinaugh et al., ). There was a strong positive edge between emotional pain and yearning, and links between meaninglessness and numbness and meaninglessness and difficulties reengaging were found to be stronger than many other in the network (see Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Specifically, “loneliness” was found to activate other symptoms through its association with loss [49] and to connect to risk factors, such as lack of instrumental social support [48]. Maccallum et al [50] analyzed the networks of depressive and complicated grief symptoms regarding 2 different types of losses (i.e., death of a spouse or a parent) in general population. The results showed that both types of losses produced very similar networks in which the strongest connection is the link between yearning and emotional pain.…”
Section: Resultsmentioning
confidence: 99%